Thematic Tafsir Study: Religious Moderation in the Qur'an and Hadith - Bayumi Nasrul Hoir (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
Islam is the religion of Rahmatan lil 'alamin brought by our apostle Muhammad (peace be upon him). If we say so, it means that we also recognize that Islam is a flexible religion. Lately we are often faced with religious issues that are quite hacking Islam itself. Islam is sometimes seen as a harsh religion, disrespectful to other religions and so on. However, is this really the case? Does Islam always punish things harshly? Of course not. Therefore, the creation of this journal aims to answer and straighten out the outstanding issues. What is the attitude of Islam towards other religions, Islam as a flexible religion and Islam as a religion that Rahmatan lil 'alamin. The method used in making this journal is to use the literature study method, which is looking for references from various books that have been recognized and trusted. Then cite the opinions stated in the book as reinforcement of this paper.